Characterization Of hydrogeological properties in Salt Lake Valley, Utah, using InSAR - Hu, Xie (2019)
Charactering subsurface aquifer systems is important not only to managing their long‐term viability as a stable water source but also to protecting the residences and infrastructures. In particular, understanding how aquifer skeletons deform in response to hydraulic head changes requires hydrogeological parameters such as decay coefficient, storage coefficient, and bulk compressibility. Quantifying these key aquifer properties often requires the analysis of limited water gauge and drilling data. Here we investigate the spatiotemporal correlation between the vertical ground deformation derived by ENVISAT Advanced Synthetic Aperture Radar (ASAR) and Sentinel‐1A data sets and available hydrological records in order to improve the aquifer characterization under Salt Lake Valley, Utah. Interferometric synthetic aperture radar results show a clear long‐term and seasonal correlation between surface uplift/subsidence and groundwater recharge/discharge, with evidence for the net uplift of 15 mm/year of an area southwest of Salt Lake City for six years. The long‐term uplift, bounded by faults and contained within the water discharge area, reflects a net increase in pore pressure associated with prolonged water recharge probably decades ago. The distribution of both previously mapped faults and newly mapped faults within the fields of deformation and the decay coefficient suggests that the faults disrupt the groundwater flow and partition the hydrological units. We also characterize human‐ and hydrological‐triggered deformation by the features of seasonality and the deviation from the exponentially decaying model. By improving our ability to characterize aquifer structures, interferometric synthetic aperture radar analysis of surface deformation in combination with traditional hydrological monitoring data presents an opportunity to recognize and mitigate potential hazards.